Parental Adherence to Ideal Cardiovascular Health Status Was Associated With a Substantially Lower Prevalence of Overweight and Obesity in Their Offspring Aged 6–18 Years - Li, Yanhui; Gao, Di; Yang, Zhaogeng; Ma, Ying; Chen, Manman; Ma, Jun; Dong, Yanhui; Dong, Bin (Frontiers in Nutrition, 2021)
Background: Parental health status had a potential influence on offspring health. This study aimed to investigate the separate associations between paternal and maternal cardiovascular health status and prevalence of childhood overweight and obesity in the offspring. Methods: Data were from a cross-sectional study conducted in 7 provinces or cities of China in 2013. 29,317 children aged 6-18 years old and their parents, making up 9,585 father-offspring pairs and 19,732 mother-offspring pairs, were included in the final analysis. Information on parental cardiovascular health status factors (dietary behaviors, BMI, smoking, physical activity, hypertension, and diabetes mellitus) was obtained from structured self-administrated questionnaires. Based on the health status factors, we then generated an ideal cardiovascular health (iCVH) score. Children’s overweight and obesity were defined using age-and sex-specific cutoffs based on the International Obesity Task Force (IOTF) criteria. A multilevel log-binomial regression model was used to assess the association between parental cardiovascular health status and prevalence of childhood overweight and obesity in the offspring. Results: The prevalence of pediatric overweight and obesity was 22.0% in the father-offspring subset and 23.8% in the mother-offspring subset, respectively. Fathers with ideal BMI, non-smoking, absence of hypertension and diabetes, and mothers with ideal BMI, ideal physical activity, absence of hypertension and diabetes were found to be associated with lower prevalence of overweight and obesity in the offspring. The prevalence of offspring overweight and obesity was significantly decreased with the parental iCVH scores increased. Each additional increase in paternal and maternal iCVH factor was associated with a 30% and 27% lower prevalence of overweight and obesity in the offspring. Compared with children whose parental iCVH scores ≤ 3, offspring whose fathers or mothers met all six iCVH factors had 67% (PR: 0.33, 95%CI: 0.25-0.42) and 58% (PR: 0.42, 95%CI: 0.29-0.62) lower prevalence of overweight and obesity, respectively. Conclusions: Parental adherence to ideal cardiovascular health status was associated with a lower prevalence of pediatric overweight and obesity in offspring. Our findings support the intervention strategy that parents should involve in the obesity intervention program for children.